Generalized quasi-likelihood approach for analyzing longitudinal count data of number of visits to a diabetes hospital in Bangladesh (Bangladesh Journal of Scientific Research, 2016)
The generalized quasi-likelihood (GQL) estimation approach has been used to analyze the longitudinal data of four repeated count responses of 872 registered diabetic patients. The data on variables such as age, sex, body mass index, family history of diabetes (heredity), area of residence, education level and physical exercise are obtained. It was aimed at proposing the GQL approach for analyzing longitudinal count data and to determine the factors related to the visits of diabetic patients at hospital. The heredity, gender, area of residence, physical exercise and age < 40 years are the potential factors to visit the hospital. It reveals that the patients who are below 40 years old, do physical exercise and whose ancestors have or had diabetes visit more to the hospital than the patients who are between 40 and 60 years old, do not exercise and whose ancestors did not have diabetes, respectively but the patients who are male and live in urban area visit less to the hospital than the patients who are female and live in rural area, respectively.Bangladesh J. Sci. Res. 29(1): 1-9, June-2016